MOTIVATION TO RECEIVE HIGHER EDUCATION: THE RESULTS OF STUDENT POLL (COMPARATIVE ANALYSIS) - Olga I. Krushelnitskaya; Antonina N. Tret'yakova (Moscow Polytechnic University, 2017)
The motivation to get higher education has a significant impact on the development of students' professional competencies. The purpose of the article was to identify the main students' motives for receiving higher education and to analyze dynamics of the motivation from the first-year study to the final year. The method of direct ranking was used. The leading motives for getting higher education for freshmen and for graduates are the following: to ensure a good financial position in the future and to become a good professional. The least magnitude for both categories of respondents have such motives as a free student life and a diploma as a document. The importance of the motives "to enhance the cultural level" and "the possibility to develop worldview" has significantly increased during the training period, while the significance of the motives «to become a respected person, to raise social status» and «to become a leader and to have power » has decreased.